A relief supplies purchasing model based on a put option contract. (January 2019) - Hu, Zhongquan; Tian, Jun; Feng, Gengzhong
Highlights: Apply put option contracts to relief supply management to solve inventory risk. Achieve the characteristics of the put option contract. Develop the condition that brings about relief supply chain coordination. Make comparisons between the option contract and other two contracts. Provide the feasible set of option price which makes both members better off. Abstract: Relief supply management is one of the most important parts in emergency management. Because of high uncertainty and time urgency, relief supplies should be purchased in advance as stock before disasters occurs. The purchasers of relief supplies are mainly governments. As in commercial supply management, governments face inventory risk and stock-out risk in their management of relief supplies. Stock-out risk can be solved by spot markets and in-kind donations, while there is no good solution to inventory risk. It is highly possible that pre-reserved relief supplies are not used within their validity periods because of the low frequency of disasters, which causes huge losses to governments. To solve the problem, we introduce a put option contract into relief supply management by considering the system as a relief supply chain. We explore the characteristics of the put option contract and prove that it can provide coordination of the relief supply chain. Furthermore, we make comparison between the put option contract, wholesale price contract and buyback contract under the same conditions to show the superiority of the put option contract. Meanwhile, we also present the condition that both a government and a supplier conduct transactions and achieve a win-win situation based on the put option contract.